Controlling factors of the metallogenic intensity in Han–Xing-type skarn iron deposits: insights from trace elements in magmatic magnetite - Yanan, Jin; Denghong, Wang; Juquan, Zhang; Long, Zhang (Frontiers in Earth Science, 2025)
The Handan–Xingtai region is one of the important production areas of skarn-type iron deposits in China. The magmatic rocks associated with iron mineralization in this region are predominantly intermediate-basic and intermediate-felsic in composition, and different intrusive complexes exhibit distinct metallogenic intensity. This study focuses on the major and trace-element geochemical analysis of magnetite in the Kuangshan and Fushan complexes to explore the controlling factors of the metallogenic intensity of Han–Xing-type skarn iron deposits. Through partial least squares discriminant analysis (PLS-DA) and orthogonal partial least squares discriminant analysis (OPLS-DA), it has been found that magnetite in the Kuangshan complex is enriched in Ti, Si, Cu, and Mn but depleted in V, Cr, Ni, Co, Ga, Al, and Mg. In contrast, magnetite in the Fushan complex is characterized by high concentrations of Co, Ni, Cr, and V. The results of mineral geochemical analyses indicate that the Kuangshan complex experienced plagioclase fractional crystallization and was formed in a low-temperature, high-oxygen fugacity environment, derived from cognate magma through crystallization differentiation. The Fushan complex is the product of non-cognate magma evolution and was formed in a low-oxygen fugacity environment. Therefore, the chemical composition of magnetite can serve as an effective tool for studying the enrichment mechanism of skarn-type iron deposits. At the same time, a high fO2 environment is conducive to the precipitation and migration of Co from magnetite, which is more favorable for the formation of associated Co deposits during the later sulfide stage.